Disparities in Educational Access in the Time of COVID: Evidence From a Nationally Representative Panel of American Families - Shira K. Haderlein; Anna Rosefsky Saavedra; Morgan S. Polikoff; Daniel Silver; Amie Rapaport; Marshall Garland (SAGE Publishing, 2021)
We use data collected between April 2020 and March 2021 from the Understanding America Survey, a nationally representative internet panel of approximately 1,450 households with school-age children, to document the access of American households to K-12 education during the COVID-19 crisis. We also explore disparities by parent race/ethnicity, income, urbanicity, partisanship, and grade level (i.e., elementary school vs. middle/high school). Results shed light on the vectors of inequality that occurred throughout the pandemic in access to technology, instruction, services (e.g., free and reduced-price meals), and in-person learning opportunities. Our work highlights the equity implications of the pandemic and suggests the importance of encouraging widespread in-person learning opportunities and attendance by the beginning of the 2021-2022 school year for addressing COVID-19's educational effects.